Intranasal drug delivery in pediatric emergency departments: brief review and future outlook - Christopher Hugh McClean; Mohammad Hussein Alsabri; Sania Tahir; Rebecca Song; Christopher Chin (Pediatric Emergency Medicine Journal, 2023)
This review aims to provide an overview and update of current literature on the use of intranasal (IN) drug delivery in pediatric emergency medicine (PEM), in terms of the anatomy, physiology, pharmacokinetics, limitations, drug delivery methods, necessary training, safety, contraindications, effectiveness, current indications and trends, and implications for clinical practice and future developments in IN drug administration. We evaluate how IN medication use in PEM has recently evolved, what recent research has revealed about the utility of IN drug delivery in PEM, and what the future of IN drug delivery might look like.